The Value and Cost of Mandatory Personal Therapy - Avis, Tami (European Journal for Qualitative Research in Psychotherapy, 2011)
Counselling psychology trainees, in the UK, are obliged to undertake a minimum of 40 hours of per- sonal therapy as part of their DPsych course requirements. This requirement creates some stress and remains controversial in the profession at large. This paper constitutes part of a wider doctoral study on how this mandatory therapy is experienced from the perspectives of both trainees and counselling psy- chologists who have trainees as clients. Interpretative Phenomenological Analysis (IPA) was employed to access the lived experience of four trainees and four qualified psychologists. Four overarching cate- gories common to the two groups were identified in the broader study: impact of mandatory therapy on therapeutic process; the therapeutic performance; the value of therapy and; boundaries. Whilst many trainees felt that therapy should remain a compulsory course requirement, they also highlighted that it costs them both emotionally and financially. I had not included questions regarding finance in my origi- nal interview schedules and did not anticipate that both trainees and therapists would mention finance so often and so fervently. Consequently in this paper, I am selectively focusing on the financial and emo- tional side of mandatory personal therapy. This article will concentrate solely on the findings related to the emotional and financial impact of mandatory personal therapy on trainees and their therapists.